Efektivitas metode Al-Haya dalam meningkatkan kemampuan membaca Alquran pada remaja yang malu - Arief, Zainal Abidin; Sudrajat,; Handrianto, Budi (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2023)
The study aims to examine the differences in the ability to read the Koran between the al-Haya method and the Iqro method based on the level of adolescent confidence. The research method used was experimental research with a 2x2 factorial design. Data collection using instruments measuring adolescent self-confidence and test instruments to read the Qur'an. Data analysis techniques used were the Two-Way ANOVA technique, the N-Gain Score test, and the Independent Sample t-Test. The results showed that: 1) there was a significant difference between the ability to read the Qur'an of adolescents who used the independent method and those who used the Iqro method. The effectiveness of the al-Haya method in improving the ability to read the Qur'an in adolescents is in the medium category, while the Iqro method is in the low category; 2) there is an interaction between the learning method of reading the Qur'an and adolescent confidence, with an estimated average margin of 60–70; and 3) there is no significant difference in the ability to read the Qur'an between adolescents with high self-confidence who use the al-Haya method and those who use the Iqro method. The effectiveness of the al-Haya method and the Iqro method in improving the ability to read the Qur'an in adolescents with high confidence is in the medium category. 3). There is a significant difference in the ability to read the Qur'an between low-confidence teenagers who use the al-Haya method and those who use the Iqro method with moderate and low levels of effectiveness. Abstrak Penelitian bertujuan untuk menguji perbedaan kemampuan membaca Al-Quran antara metode al-Haya dan metode Iqro berdasar pada tingkat kepercayaan diri remaja. Metode penelitian yang digunakan adalah penelitian eksperimen dengan desain 2x2 faktorial. Pengumpulan data menggunakan instrumen pengukuran kepercayaan diri remaja dan instrumen tes kemampuan membaca Alquran. Teknik analisis data menggunakan teknik Two Way Anova, uji N-Gain Score dan uji Independent Sample t Test. Hasil penelitian menunjukkan bahwa: 1) terdapat perbedaan yang signifikan antara kemampuan membaca Alquran remaja yang menggunakan metode al-Haya dengan yang menggunakan metode Iqro. Efektivitas metode al-Haya dalam meningkatkan kemampuan membaca Alquran pada remaja berada pada kategori sedang, sementara metode Iqro pada kategori rendah; 2) terdapat interaksi antara metode pembelajaran membaca Alquran dengan kepercayaan diri remaja, dengan estimasi margin rata-rata pada angka 60-70; 3) terdapat perbedaan kemampuan membaca Alquran yang tidak signifikan antara remaja kepercayaan diri tinggi yang menggunakan metode al-Haya dengan yang menggunakan metode Iqro. Efektivitas metode al-Haya dan metode Iqro dalam meningkatkan kemampuan membaca Alquran pada remaja dengan kepercayaan diri tinggi berada pada kategori sedang. 3). Terdapat perbedaan kemampuan membaca Alquran yang signifikan antara remaja berkepercayaan diri rendah yang menggunakan metode al-Haya dengan yang menggunakan metode Iqro dengan tingkat efektivitas sedang dan rendah.